Analisis Strategi Pengembangan Usahatani Kakao - Utami, Yulistiana Endah; Maarif, Mohamad Syamsul; Fahmi, Idqan; suroso, arif imam (Universitas Jambi, 2019)
Indonesia has the hope of becoming the world's largest cocoa producer and has a strong cocoa processing industry in the world. The challenge is the production of cocoa beans produced cocoa farming can not meet the needs of the raw materials processing industry in the country, so there is a gap between the production of cocoa beans from the farm to the need / demand for raw materials cocoa beans from the cocoa processing industry in the country. This study aimed to conduct development strategy formulation cocoa farming in Indonesia. The formulation of strategies in this study was based on justification from stakeholders using Analytic Hierarchy Process (AHP) analysis tools. The results from the AHP analysis showed that the most effective strategy for the development of cocoa farming in the study regions is the development of farmer institutions and assistance in applying technology (weight value of 0.309). The most important objective for the development of cocoa farming is to increase the production and quality of cocoa beans (weight value of 0.503). The key actor who plays an important role in the development of cocoa farming is the government, both central and local (weight value of 0.269). The most important factor to be considered in the development of cocoa farming is human resources (weight value of 0.193). Based on these results, it is recommended to strengthen the development of cacao farmers through a form of business entity owned by farmers who are accompanied by the government